Analysis of Factors Affecting the Performance of Emergency Nurses in Bhayangkara Tebing Tinggi Public Hospital - Vera Agustina; Ismail Efendy; Masnelly Lubis (Journal La Medihealtico, 2020)
Emergency Room (IGD) as one of the first entry points for patients to the hospital, will indirectly provide an overview of hospital services as a whole. Data on emergency visits of patients at Bhayangkara Tebing Tinggi Hospital in the January - May 2020 period were 2,685 patients and experienced a significant decrease every month. The research objective was to analyze the factors that influence the performance of emergency room nurses at the Tebing Tinggi Bhayangkara General Hospital in 2020. The research design used a descriptive analytic method with a cross-sectional approach. The population in the study were all nurses who served in the IGD at the Bhayangkara Tebing Tinggi Hospital in 2020 totaling 32 people. The sample uses the otal population. Data analysis used univariate, bivariate and multivariate analysis using logistic regression tests.The results of the study using logistic regression showed the sig. each variable, namely the variable ability (0.578), skills (0.011), motivation (0.129), reward (0.013), infrastructure (0.855) and the value of Exp (B) the largest = 26.633 in the variable reward. The conclusion of this study is that there is a significant effect of skills and rewards on the performance of nurses in the IGD at the Bhayangkara Tebing Tinggi Hospital and the variables that have no significant effect are ability, motivation and infrastructure.